Pengaruh Profitabilitas, Ukuran Perusahaan dan Kepemilikan Publik pada Pengungkapan Corporate Social Responsibility - Windra Lorna Pramesti, Anak Agung; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2020)
This study aims to influence profitability on corporate social responsibility disclosure, the effect of company size on corporate social responsibility disclosure, the effect of public ownership on corporate social responsibility disclosure. The study was conducted on mining companies that were officially listed on the Indonesia Stock Exchange (BEI) in 2015-2017. The population in this study were all mining companies listed on the Indonesia Stock Exchange from 2015-2017. The sample used by purposive sampling. The data analysis technique used is multiple linear regression analysis. The results showed that profitability, company size and public ownership had a positive effect on the disclosure of Corporate Social Responsibility. Keywords: Profitability; Company Size; Public Ownership; Corporate Social Responsibility.